Estimation of The Potential of Large Pelagic Fish Fisheries Using Satellite Data in The Banda and Arafura Seas - Ahkam, Muhammad Faqih; Tarya, Ayi (Devotion : Journal of Research and Community Service, 2023)
The Banda and Arafura Sea possesses significant potential for the fisheries and fishing industry in the country. The large pelagic fish production data studied were derived from satellite imagery data in the Banda and Arafura Seas (2002-2022). The data of chlorophyll-a content, sea surface temperature and Photosynthetically Available Radiation (PAR) derived from AQUA MODIS satellite images were used to estimate the value of primary productivity with the Vertically Generalised Production Model (VGPM). The results showed that the biomass of large pelagic fish fluctuated seasonally, with the Banda Sea and Arafura Sea having high average fish biomass values in the eastern season. With the highest fish biomass peak in August and the lowest in December. The high value of fish biomass in the Banda Sea and Arafura Sea is caused by upwelling events where sea surface temperatures are low but chlorophyll is high. in the Arafura Sea the value of fish biomass is higher than the Banda Sea, this is due to the large amount of nutrient input from large rivers in the area.